2018
DOI: 10.3233/jnd-170276
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm: Pathophysiology and Ultrasound Imaging in Neuromuscular Disorders

Abstract: Respiratory muscles are classically involved in neuromuscular disorders, leading to a restrictive respiratory pattern. The diaphragm is the main respiratory muscle involved during inspiration. Ultrasound imaging is a noninvasive, radiation-free, accurate and safe technique allowing assessment of diaphragm anatomy and function. The authors review the pathophysiology of diaphragm in neuromuscular disorders, the methodology and indications of diaphragm ultrasound imaging as well as possible pitfalls in the interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 64 publications
0
70
1
6
Order By: Relevance
“…Diaphragm being the major respiratory drive muscle, VIDD has an adverse impact on weaning off and is associated with prolonged mechanical ventilation and hospital stay 4 . Conventional measures of diaphragmatic function such as phrenic nerve conduction study, transdiaphragmatic pressure measurement, pulmonary function testing, fluoroscopy, and diaphragmatic electrical activity, have limitations such as the need for special equipment, invasiveness, and exposure to ionizing radiations 5 . Ultrasound is a noninvasive bedside alternative for the assessment of diaphragmatic bulk and function 5 …”
Section: Introductionmentioning
confidence: 99%
“…Diaphragm being the major respiratory drive muscle, VIDD has an adverse impact on weaning off and is associated with prolonged mechanical ventilation and hospital stay 4 . Conventional measures of diaphragmatic function such as phrenic nerve conduction study, transdiaphragmatic pressure measurement, pulmonary function testing, fluoroscopy, and diaphragmatic electrical activity, have limitations such as the need for special equipment, invasiveness, and exposure to ionizing radiations 5 . Ultrasound is a noninvasive bedside alternative for the assessment of diaphragmatic bulk and function 5 …”
Section: Introductionmentioning
confidence: 99%
“…This was due to the increase of the rib cage contribution to generate more volume to counterbalance the disadvantages of positioning and diaphragmatic weakness in subjects with DMD. 4,10,49 Our results during quiet spontaneous breathing indicate that subjects with DMD presented lower chest wall tidal volume at the expense of a higher f, resulting in a higher RSBI compared with controls, as a strategy to reduce the elastic work within the breath and the perception of dyspnea. 10,50 Our results agree with those reported by Misuri et al, 50 who evaluated subjects with neuromuscular disease using a pneumotachograph, including subjects with DMD, and observed that the subjects' ventilatory pattern showed a normal _ V E , a consistent decrease in T i and T e , and an increase in f and RSBI.…”
mentioning
confidence: 75%
“…In the current study, one LOPD subject with inspiratory muscle weakness and absent C-C excursion required the use of BiPAP to image tidal breathing. Therefore, while ultrasonography can yield lower tissue resolution and an insufficient window in some patients, it may be preferred in clinical settings or to monitor moderate to severe diaphragmatic involvement 25,26 . Additionally, sniff nasal inspiratory pressure (SNIP) reflects pressure associated with a maximal effort sniff.…”
Section: Discussionmentioning
confidence: 99%